2020
DOI: 10.1186/s13102-020-00175-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Total resistance exercise vs. aquatic training on self-reported knee instability, pain, and stiffness in women with knee osteoarthritis: a randomized controlled trial

Abstract: Background: Knee Instability (KI) is described as a sense of knee buckling, shifting, or giving way during the weight bearing activities. High prevalence (60-80%) has been reported for KI amongst the patients with knee osteoarthritis (KOA). In this line, the present study targeted the effect of two interventions on self-reported KI and affected factors. Methods: In this single blind, randomized, and controlled trial, 36 patients with radiographic grading (Kellgren-Lawrence ≥ II) of KOA were selected. Patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Continuous tension of the iliotibial band can cause Iliotibial Band Friction Syndrome and cause knee pain. Studies have reported that exercise therapy has a certain effect on knee pain and knee joint function [4,23] . However, there are few studies comparing the effects of stretching and non-stretching after exercise on the improvement of the two.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous tension of the iliotibial band can cause Iliotibial Band Friction Syndrome and cause knee pain. Studies have reported that exercise therapy has a certain effect on knee pain and knee joint function [4,23] . However, there are few studies comparing the effects of stretching and non-stretching after exercise on the improvement of the two.…”
Section: Introductionmentioning
confidence: 99%
“…Application of CPM therapy in the initial rehabilitation of patient with limited ROM of the knee joint positively affected in the change of ROM and pain during the knee extension and flexion as well as reduced length of stay in hospital (Bakirhan et al, 2015;Liao et al, 2016;Yang et al, 2019). Also, recent studies reported that aquatic exercise for the treatment of knee osteoarthritis could be safe and improve pain, disability, and quality of life (Assar et al, 2020). The results of these previous studies support the importance of aquatic walking exercise in therapeutic strategy for developing the knee ROM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is unclear whether instability is the cause of imbalance or poor balance is the cause of instability. Knee instability is a multifactorial condition, which may occur due to increased capsular-ligament laxity, damage to the knee structures, decreased muscle strength, altered muscle activity patterns, and altered neuromuscular control, Therefore, insufficient joint stability is provided during daily activities and this leads to pain, swelling, and decreased mobility, and ultimately affects the patient's posture control and balance [3,4,37,38]. In a systematic review in this regard, Wallace et al (2019) reported that knee instability may occur due to the proprioception impairment or lack of posture control as the patient is unable to be clearly positioned and control the joint movement.…”
Section: Discussionmentioning
confidence: 99%